2018
DOI: 10.3126/jnbs.v11i1.24195
|View full text |Cite
|
Sign up to set email alerts
|

Rights Offering and Its Effect on Share Price Movement: A Study of Commercial Banks

Abstract: This paper examines the effect of rights share issue on share price movement in the banking sector covering the period 2007/08 to 2016/17. In order to find out the share price movement in different selected points of time, pre and post right issue and price relatives were calculated considering the price of 90 days before the right announcement date as the beginning index. Five different points of time were selected to observe the share price movements assuming the announcement date as the reference point of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Even if it is not statically significant, the another finding of study is that 100% of abnormal returns of six days; 80% of abnormal returns of ten days and 60% of abnormal returns of twelve days are negative. Pathak and Gupta (2018) conducted a research on rights offering and its effect on share price movements taking five commercial banks as sample size. In his research, he found that the right share offering announcement has the signaling effect on the share price of the commercial banks.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Even if it is not statically significant, the another finding of study is that 100% of abnormal returns of six days; 80% of abnormal returns of ten days and 60% of abnormal returns of twelve days are negative. Pathak and Gupta (2018) conducted a research on rights offering and its effect on share price movements taking five commercial banks as sample size. In his research, he found that the right share offering announcement has the signaling effect on the share price of the commercial banks.…”
Section: Review Of Literaturementioning
confidence: 99%